Osteochondral Allograft Transplantation for a Cartilage Defect of the Humeral Capitellum - Kyle R. Wagner BS; Mario Hevesi MD, PhD; Joshua T. Kaiser BS; Zachary D. Meeker BS; Brian J. Cole MD, MBA (Video Journal of Sports Medicine, 2022)
Background: Cartilage defects of the humeral capitellum most frequently present as osteochondritis dissecans (OCD) in young overhead athletes, such as baseball players. Historically, surgical options have included debridement, marrow stimulation, and osteochondral autograft transplantation. Fresh osteochondral allograft (OCA) transplantation comprises an additional treatment option that can structurally restore osteochondral defects and has demonstrated satisfactory outcomes without the donor-site morbidity associated with osteochondral autograft transplantation. Indication: OCA transplantation provides structural restoration of the articular surface and can be used for large (>1 cm diameter) lesions not amenable to refixation. Additionally, OCA transplantation can address both chondral and subchondral pathology and is suited for the treatment of failed previous surgical interventions, such as debridement or marrow stimulation. Technique Description: Following diagnostic arthroscopy, an anconeus splitting mini-open approach was performed to expose the capitellar defect. The defect was measured to be 10 mm, and a central guide pin was placed. A 10-mm reamer was used to prepare the defect bed to a depth of 8 mm. An OCA plug was then cut from a fresh femoral hemicondyle to match the prepared defect. The graft was soaked in bone marrow aspirate concentrate harvested from the iliac crest, and the plug was then inserted into the defect and tamped to be concentric with the surrounding articular cartilage. Results: OCA transplantation of the capitellum allows for the restoration of the articular surface with a structural graft and can be used for large defects and revision cases. While OCA transplantation is well described in the knee with long-term efficacy, the application of this technique to the capitellum is relatively recent. Recent case series for the capitellum have displayed significant improvements in patient-reported outcome measures and predictable return to sports. Discussion/Conclusion: OCA transplantation for the humeral capitellum provides an effective treatment option for large, unstable cartilage lesions not amenable to refixation. The procedure allows for restoration of the articular surface and can provide improvements in pain and function as well as return to sport.